TOXICO EPIDEMIOLOGY OF LEAD, NICKEL AND CADMIUM LEVELS IN SHEEP SERUM OF AL BASRAH PROVINCE - Rashad F.Ghadhban; Mohammad R.S.Alattabi; Nameer A.Kareem Alzubaidi (Basrah Journal of Veterinary Research)
The comparison toxico-epidemiological study designed to evaluate the Lead, Nickel and Cadmium levels in healthy sheep of different regions in Al Basrah province and compared with sheep from Animal Farm of Agriculture College /University of Basrah(as control group). Sixty three adult male sheep were tested for the study (6 animals for each region). Blood samples were collected from each ram, the Pb, Ni and Cd values were measured. AST, ALT and creatinine values were also determined. The results revealed to high increase levels of Cd, and Pb concentration among the different regions and compared with control rams values. There were no significant differences in the transaminase enzymes activity and creatinine concentration among the animals tested. In spite of the rise in trace minerals values but it did not threshold to harmful effect on rams’ body physiology.